MUC1-C is a master regulator of MICA/B NKG2D ligand and exosome secretion in human cancer cells. Issue 2 (8th February 2023) - Morimoto, Yoshihiro; Yamashita, Nami; Daimon, Tatsuaki; Hirose, Haruka; Yamano, Shizuka; Haratake, Naoki; Ishikawa, Satoshi; Bhattacharya, Atrayee; Fushimi, Atsushi; Ahmad, Rehan; Takahashi, Hidekazu; Dashevsky, Olga; et al.
Abstract : Background: The MUC1-C protein evolved in mammals to protect barrier tissues from loss of homeostasis; however, MUC1-C promotes oncogenesis in association with chronic inflammation. Aberrant expression of MUC1-C in cancers has been linked to depletion and dysfunction of T cells in the tumor microenvironment. In contrast, there is no known involvement of MUC1-C in the regulation of natural killer (NK) cell function. Methods: Targeting MUC1-C genetically and pharmacologically in cancer cells was performed to assess effects on intracellular and cell surface expression of the MHC class I chain-related polypeptide A (MICA) and MICB ligands. The MICA/B promoters were analyzed for H3K27 and DNA methylation. Shedding of MICA/B was determined by ELISA. MUC1-C interactions with ERp5 and RAB27A were assessed by coimmunoprecipitation and direct binding studies. Exosomes were isolated for analysis of secretion. Purified NK cells were assayed for killing of cancer cell targets. Results: Our studies demonstrate that MUC1-C represses expression of the MICA and MICB ligands that activate the NK group 2D receptor. We show that the inflammatory MUC1-C→NF-κB pathway drives enhancer of zeste homolog 2-mediated and DNMT-mediated methylation of the MICA and MICB promoter regions. Targeting MUC1-C genetically and pharmacologically with the GO-203 inhibitor induced intracellular and cell surface MICA/B expression but not MICA/B cleavage. Mechanistically, MUC1-C regulates the ERp5 thiol oxidoreductase that is necessary for MICA/B protease digestion and shedding. In addition, MUC1-C interacts with the RAB27A protein, which is required for exosome formation and secretion. As a result, targeting MUC1-C markedly inhibited secretion of exosomes expressing MICA/B. In concert with these results, we show that targeting MUC1-C promotes NK cell-mediated killing. Conclusions: These findings uncover pleotropic mechanisms by which MUC1-C confers evasion of cancer cells to NK cell recognition and destruction.